The nature of the electron acceptor (MnIV/NO3) triggers the differential expression of genes associated with stress and ammonium limitation responses in Shewanella algae C6G3. Issue 13 (16th March 2018) - Aigle, Axel; Bonin, Patricia; Fernandez-Nunez, Nicolas; Loriod, Béatrice; Guasco, Sophie; Bergon, Aurélie; Armougom, Fabrice; Iobbi-Nivol, Chantal; Imbert, Jean; Michotey, Valérie
Abstract: Shewanella algae C6G3 can dissimilatively reduce nitrate into ammonium and manganese oxide (MnIV) into MnII. It has the unusual ability to anaerobically produce nitrite from ammonium in the presence of MnIV. To gain insight into their metabolic capabilities, global mRNA expression patterns were investigated by RNA-seq and qRT-PCR in cells growing with lactate and ammonium as carbon and nitrogen sources, and with either MnIV or nitrate as electron acceptors. Genes exhibiting higher expression levels in the presence of MnIV belonged to functional categories of carbohydrate, coenzyme, lipid metabolisms and inorganic ion transport. The comparative transcriptomic pattern between MnIV and NO3 revealed that the strain presented an ammonium limitation status with MnIV, despite the presence of a non-limiting concentration of ammonium under both culture conditions. In addition, in the presence of MnIV, ntrB/nrtC regulators, ammonium channel, nitrogen regulatory protein P-II, glutamine synthetase and asparagine synthetase glutamine-dependent genes were over-represented. Under the nitrate condition, the expression of genes involved in the synthesis of several amino acids was increased. Finally, the expression level of genes associated with the general stress response was also amplified in both conditions and among them, katE, a putative catalase/peroxidase present on several Shewanella genomes, was highly expressed with a median value relatively higher in the MnIV condition. Abstract : Shewanella algae C6G3 can conduct dissimilative nitrate reduction into ammonium and Mn-oxide reduction but this latter respiration affects ammonium assimilation and induces a specific stress response.